Agricultural management of an Oxisol affects accumulation of heavy metals. (October 2017) - Minari, Guilherme Deomedesse; Rosalen, David Luciano; da Cruz, Mara Cristina Pessôa; de Melo, Wanderley José; Alves, Lucia Maria Carareto; Saran, Luciana Maria
Abstract: Soil contamination may result from the inadequate disposal of substances with polluting potential or prolonged agricultural use. Therefore, cadmium (Cd), chromium (Cr) and nickel (Ni) concentrations were assessed in a Eutroferric Red Oxisol under a no-tillage farming system with mineral fertilizer applications, a conventional tillage system with mineral fertilizer application and a conventional tillage system with sewage sludge application in an area used for agriculture for more than 80 years. We evaluated the spatial distributions of these elements in the experimental area and the effect of the different management practices on the soil retention of these metals. The concentrations of metals extracted from 422 soil samples by open-system digestion with HNO3, H2 O2 and HCl were assessed by flame atomic absorption spectroscopy. The pH and soil organic matter were also assessed, and spatial distribution maps were designed. The mean concentrations of Cd, Cr and Ni (1.0, 50 and 14 mg kg −1, respectively) in the native forest were higher than the reference values (100, 25 and 8% greater, respectively) in Brazilian legislation, indicating that the source material was the determining factor of the high metal concentrations in the study soils. Soil management with sewage sludge was the major contributor to the accumulation of Cd and Ni, whereas Cr concentration did not vary with management type. Approximately 0.3, 12 and 16% of the experimental area is contaminated with Ni, Cd and Cr, respectively, because their concentrations exceeded the values for alertness or prevention in Brazilian legislation. Highlights: Cd, Cr and Ni levels in the native forest exceeded the reference quality values. 12% of the experimental area is contaminated with Cd, 16% with Cr and 0.3% with Ni. The management with sewage sludge increased the levels of Cd and Ni. The Cr content in soil was not affected by the type of management.